Faciomandibular asymmetry: An analysis of skeletal parameters and possible etiological factors - Preeti Munjal; Ashok Utreja; Sunny Mittal; Sangeeta Sunda; Nishtha Arora (Indian Journal of Dental Sciences, 2017)
Aim and Objectives: The present study has been carried out in an attempt to study the asymmetries of lower one-third of face in terms of etiological factors involved, kind of presentation that it may have, and also to quantify the asymmetry on skeletal aspects. Along with, an attempt has been made to examine if any correlation exists between the severity of asymmetry and presenting age, age of trauma (TrAge), and lag period (LAGPrd). Materials and Methods: The present study was conducted on thirty patients (17 males and 13 females) reporting with a chief complaint of asymmetry at the Dental and Plastic Surgery OPD, PGIMER, Chandigarh, over a period of 2 years. A descriptive pro forma to record signi fi cant medical and dental history was filled to correlate possible etiological factors to the presenting complaint. Along with, posteroanterior cephalogram and orthopantomograms were recorded and traced with speci fi c parameters to correlate them with the present age, TrAge, and LAGPrd. Results: It was concluded that trauma was the single most important possible etiologic factor responsible for facial asymmetry. Assymetry was more apparent in lower third of the face with deviation of chin, fullness of one side and flatness of the other. OPG revealed vertical height of ramus and depth of antegonial notch are affected by trauma and deformity increases with LAGPrd increase. PA cephalogram co-related with similar findings. Conclusion: Faciomandibular asymmetry resulted due to undergrowth or overgrowth of the affected part of mandible. On OPG significant asymmetry was observed which increased with the lag period (difference between age of presenting and age of trauma).